Applied technology integration in governmental organizations new e-government research - Weerakkody, Vishanth (Information Science Reference, 2011)
"This book provides organizational and managerial directions to support the greater use and management of electronic or digital government technologies in organizations, while epitomizing the current e-government research available"--Provided by publisher.